Hubungan antara kecerdasan emosional dengan kecenderungan burnout pada karyawan bagian pemasaran - Widjaja, Madeline S.; Sitorus, Kartika S.; Himawan, Karel K. (Konsorsium Psikologi Ilmiah Nusantara, 2016)
Working is a stage in the path of life each human will pass. However, during employment, a person may experience pressure and if the pressure persists, the situation may tend to lead to burnout. Burnout is a syndrome of emotional fatigue due to excessive working demands. The effect of burnout is not only experienced physically, but also psychologically. Burnout is caused by numerous factors, both external and internal. Internal factor includes emotional intelligence. The purpose of this study was to observe and identify the correlation between emotional intelligence and burnout tendency of employees in the marketing department. This study adopted 104 samples and data are collected through questionnaires. Based on the statistical tests conducted, significant correlation exists between emotional intelligence and burnout tendency of employees in the marketing department. The correlation was negative, implying that the higher the emotional intelligence employees have, the lower the burnout tendency they may have, and vice versa.